Effects of Melatonin and Citric Acid Foliar Application and their Interaction on Growth and Yield of Local Barley Hordeum Vulgare L. - Mohammed, Saja Abdullah; Aljasimee, Kawther Hashim Abar; Mousa Mazene, Lamyaa Hussein (American Journal of Biology and Natural Sciences, 2026)
A field experiment was conducted during the 2025-2026 winter growing season in the Sumer district to determine the effect of foliar spraying of melatonin and citric acid, and their interaction, on some growth and yield attributes of local barley varieties. The experiment was conducted as a factorial experiment with two factors and three replications. The first factor was melatonin spraying (M0: no spray, M1: 25, M2: 50) mg/L⁻¹, while the second factor was citric acid spraying (C0: no spray, C1: 1, C2: 2) g/L⁻¹. the results of statistical analysis showed that the melatonin and citric acid spraying treatments, each separately, recorded significant differences of all studied attributs, such as plant height, spike length, leaf area, number of spikes per plant, weight of 1000-grain, grain yield, straw yield, and biological yield. As for the interaction between melatonin and citric acid spraying M2C2 treatment was one of the best experimental treatments, as it significantly exceeded on them and recorded the highest means of all the mentioned attributes. Hence we conclude that spraying with melatonin and citric acid had a best effect on the growth performance and yield of the local barley crop.